THE IMPACT OF ACCESS TO DENTAL SERVICE ON PUBLIC HEALTH: A LITERATURE REVIEW - Darmadi, Eveline Yulia; Fauziah, Yessy Andriani; Sanjaya, Maria Laurentia (HEARTY, 2025)
Access to dental services is critical in determining public health status, yet significant disparities persist, especially in remote areas. This literature review explores the impact of limited access to dental care on public health. The review methodology involved analyzing recent studies addressing the various factors—economic, geographical, and social determinants—influencing access to dental services in different communities. The results indicate that individuals with restricted access to dental care are more prone to oral diseases, which can lead to a decline in overall health and quality of life. Furthermore, these communities often face higher treatment costs due to the need for more complex procedures when issues are untreated for extended periods. The findings highlight that limited access to dental services increases the burden on healthcare systems and exacerbates inequalities in health outcomes. In conclusion, improving access to dental services, particularly in underserved and rural areas, is essential to mitigate the negative effects of oral diseases, reduce healthcare costs, and improve public health outcomes in the long term. Addressing these disparities is crucial for promoting equitable health opportunities for all.